2018
DOI: 10.1212/wnl.0000000000005063
|View full text |Cite
|
Sign up to set email alerts
|

Selective cognitive impairment and hyposmia in p.A53T SNCA PD vs typical PD

Abstract: The observed selective cognitive impairment reflecting frontal-parietal network dysfunction, together with impaired olfaction, define a set of nonmotor dysfunctions related to A53T PD. These results have implications for the prognosis of patients with A53T PD. Moreover, as the archetypal α-synucleinopathy, such results may give insights into tPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 12 publications
3
17
1
Order By: Relevance
“…However, scores in certain neuropsychological tests involving working memory were inferior in the p.A53T‐PD cohort. These tests reflect mainly frontal executive functions and recapitulate our findings in a larger cohort of p.A53T carriers . Despite the fact that no correlation between neuropsychological scores and caudate nucleus dopaminergic denervation could be demonstrated in our study, recent reports indicate that caudate uptake on 123I‐FP‐CIT SPECT imaging is among the 5 variables showing the most significant associations with cognitive impairment (along with age, UPSIT (University of Pennsylvania Smell Identification Test) olfaction test, Rapid Eye Movement Sleep Behavior Disorder Screening Questionnaire, and CSF β‐amyloid Aβ42), which allowed the prediction of cognitive impairment at 2 years post–initial evaluation in PD patients .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, scores in certain neuropsychological tests involving working memory were inferior in the p.A53T‐PD cohort. These tests reflect mainly frontal executive functions and recapitulate our findings in a larger cohort of p.A53T carriers . Despite the fact that no correlation between neuropsychological scores and caudate nucleus dopaminergic denervation could be demonstrated in our study, recent reports indicate that caudate uptake on 123I‐FP‐CIT SPECT imaging is among the 5 variables showing the most significant associations with cognitive impairment (along with age, UPSIT (University of Pennsylvania Smell Identification Test) olfaction test, Rapid Eye Movement Sleep Behavior Disorder Screening Questionnaire, and CSF β‐amyloid Aβ42), which allowed the prediction of cognitive impairment at 2 years post–initial evaluation in PD patients .…”
Section: Discussionsupporting
confidence: 85%
“…It is possible that these findings may not reflect true preferential effects on the caudate, as differences between putaminal binding ratios may have been underestimated due to a floor effect. Altogether, this pattern of striatal dopaminergic denervation might implicate a more aggressive disease course in p.A53T mutation carriers, as evidenced by a requirement for higher LEDD despite similar disease duration and our previous findings of more pronounced deficits in specific PD‐associated cognitive domains and olfaction in a larger group of p.A53T SNCA PD patients . It is also possible that the preferential effects on the caudate binding ratios reflect a differential topography of nigrostriatal degeneration in the mutation carriers when compared with PD.…”
Section: Discussionsupporting
confidence: 63%
“…The pattern of distribution of LBs followed broadly that of sporadic PD cases, and this pathology also had a clinical correlate paralleling sporadic disease. In this respect, it is worth mentioning that cases harbouring the A53T mutation have prodromal symptoms including olfactory dysfunction, depression, gastrointestinal dysfunction, and rapid eye movement (REM) sleep behaviour disorder (RBD) at the same frequency or even more than in sporadic disease [94], likely reflecting a very similar LB pathology distribution. While cases with missense mutations could have variable LB extension and some mutations appear to be more aggressive than others, a clearer dose effect is found in CNVs cases, whereas although in general terms showed typical LB pathology, duplication cases showed more frequently brainstem restricted disease that correlated with an akinetic–rigid syndrome and triplication cases showed a diffuse disease that correlated with dementia.…”
Section: Intrinsic Cellular Properties Underlying Selective Vulnerabimentioning
confidence: 99%
“…Though OD in PD presents non-uniformly, community-based prospective studies demonstrated that it can appear up to 4 years before motor-symptom onset (79,80); in MAPT carriers it can appear 2 years before symptom onset (52). Consequently, OD has been used in biomarker panels for predicting risk and/or progression of PD [ (59,(82)(83)(84)(85)(86)(87)(88); reviews: (18,19,(89)(90)(91)]. For this purpose, it is important to elucidate: (1) whether OD in PD is distinguishable from OD in other diseases and aging; (2) how its onset and progression relates to motor-symptom onset and progression; (3) whether OD severity is associated with disease stage, duration, or predicts disease progression; and 4what clinical tests of OD measure in the context of the disease process.…”
Section: Od Characteristics In Pdmentioning
confidence: 99%
“…The use of shared neural substrates in the premotor frontal and orbitofrontal cortex by olfaction and cognition (Figure 2), and the contribution of cholinergic deficits to OD provides a potential mechanism for why greater OD appears to identify the subset of sporadic and monogenic PD patients at greater risk of future cognitive impairment [ (59,107,(139)(140)(141)(142)(143)(144)(145)(146)(147)(148)(149); reviews: (27,150)]. Thus, genome-wide screens in PD subjects for variants that influence risk of severe OD or protect from developing OD may identify genetic factors that increase risk of, or offer protection from, cognitive impairment in PD.…”
Section: How Is Od Related To Disease Onset and Progression?mentioning
confidence: 99%